2008
DOI: 10.3748/wjg.14.6970
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors affecting pancreatic fistulas after pancreaticoduodenectomy

Abstract: AIM:To analyze the risk factors of pancreatic leakage after pancreaticoduodenectomy. METHODS:We r e t r o s p e c t i v e l y r e v i e w e d 1 7 2 consecutive patients who had undergone pancreaticoduodenectomy at Inha University Hospital between April 1996 and March 2006. We analyzed the pancreatic fistula rate according to the clinical characteristics, the pathologic and laboratory findings, and the anastomotic methods. RESULTS: The incidence of developing pancreatic fistulas in patients older than 60 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 27 publications
2
37
2
Order By: Relevance
“…Of the many types of complications that occur after PD, pancreatic fistula was the most significant and complicated. Previous studies revealed that the pancreatic fistula rate following resection of nonampullary duodenal tumors is 10-63% [27][28][29][30][31][32][33][34]. In our study, the pancreatic fistula rate for duodenal GISTs treated with PD was 14.3%, which is in the range mentioned in previous reports.…”
Section: Discussionsupporting
confidence: 76%
“…Of the many types of complications that occur after PD, pancreatic fistula was the most significant and complicated. Previous studies revealed that the pancreatic fistula rate following resection of nonampullary duodenal tumors is 10-63% [27][28][29][30][31][32][33][34]. In our study, the pancreatic fistula rate for duodenal GISTs treated with PD was 14.3%, which is in the range mentioned in previous reports.…”
Section: Discussionsupporting
confidence: 76%
“…Reported risk factors of POPF in PD in patients older than 60 years of age include nondilated duct size, longer operative time, greater intraoperative red blood cell transfusions, lower surgical volume, and soft texture. [9][10][11] With regard to the anastomotic procedure, duct-to-mucosa pancreaticojejunostomy and external drainage of the pancreatic duct with a stent have been recommended; 12 the efficacy of those procedures, however, remains controversial. In DP, we previously cut the stump of the remnant pancreas using a knife, then subsequently ligated the main pancreatic duct and sutured the tissue of the pancreas to close.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these approaches have been met with varying success. Others have developed prognostic scores to predict the risk of POPF [11,12,[29][30][31]. Although, both Braga and Callery scores are useful tools in predicting complications and POPF after OPD, respectively, they have not been validated for minimally invasive approaches.…”
Section: Discussionmentioning
confidence: 99%